Shared leadership and team motivation: An exploratory study - CHI, Yufeng (Institutional Knowledge at Singapore Management University, 2019)
Despite the importance of team innovation for organizations, the conditions that foster team innovation are still not well understood. In this dissertation, I propose a theoretical model in which the impact of shared leadership on team innovation is mediated by information sharing and team potency. I utilize a two-wave longitudinal, multi-method and multi-source research design to examine the research hypotheses. I argue that shared leadership not only improves a team’s information sharing and team potency, but also generates cognitive and motivational advantages that are conducive to innovation. In addition, I show that the relationship between shared leadership and team innovation is moderated by leader-member exchange (LMX) differentiation, and the innovation stage moderates the relationship between shared leadership and team potency. LMX differentiation restrains the positive effect of shared leadership on information sharing and team potency because high LMX differentiation increases perceived injustice in teams. The results show that team potency mediates the impact of shared leadership on team innovation. The positive impact of information sharing and team potency on team innovation is stronger in the idea implementation stage than in the idea generation stage. My research contributes to the shared leadership literature by identifying how and when shared leadership influences team innovation.